Penilaian Human Error Probability dengan Metode Human Error Assessment and Reduction Technique (HEART) (Studi di Departemen Finishing PT. Eratex Djaja, Tbk) Assessment of Human Error Probability with Human Error Assessment and Reduction Technique Method ( - Riselvia Nurhayati; Isa Ma'rufi; Ragil Ismi Hartanti (Pustaka Kesehatan, 2017)
PT. Eratex Djaja, Tbk is a company engaged in the garment industry. Working accidents that occurred in this company, 46.67% caused by human error and 61.9% of which occurred in the Finishing Department. The purpose of this research was assessment human error probability with Human Error Assessment and Reduction Technique Method (HEART) in Finishing Department of PT. Eratex Djaja, Tbk. The type of research was descriptive. In this study there were 13 respondents. The results show that the tasks in the finishing department were task keyhole, buttoning, trimming, ironing, measurement, attach accessories, finishing quality control, packing, needle detector, repack, scanning, weigh and export. There were 27 tasks that have possible human error. The largest HEP was 0.9599 in the task holding garment until the keyhole process was completed (task keyhole with automatic keyhole) and in the task holding garment until the buttoning process was complete (task buttoning plastic button). While the smallest HEP was 0,0326 in the task of transporting and bring carton box into the container. Then the researchers set up prevention of human error based on EPC, HEP and possible human error that can occur in the task or sub task.Keywords: Possible human error, HEART, HEP